Assessment of Aromatic Hydrocarbons in Urban Air: A Study from a Northern Mexican Megacity - Julia Griselda Cerón Bretón; Rosa María Cerón Bretón; Claudia Alejandra Aguilar Ucán; Carlos Montalvo Romero; Alberto Antonio Espinosa Guzmán; Simón Eduardo Carranco Lozada; Evangelina Ramírez Lara; María de la Luz Espinosa Fuentes; Martha Patricia Uc Chi (Atmosphere)
The spatiotemporal distributions of aromatic hydrocarbon levels in the atmosphere were evaluated at ten locations within Monterrey’s Metropolitan Area using passive sampling techniques across three climatic seasons (the rainy season of 2023, the cold front season of 2023, and the dry season of 2024). The observed relative abundance was toluene > p-xylene > benzene > ethylbenzene. The dry season showed the highest concentration values for all measured compounds, and the Santa Catarina site showed the highest average level for toluene (2.79 μg m−3). In the rainy season, the highest average concentrations were recorded in Santa Catarina, with toluene at 1.39 μg m−3 and p-xylene at 0.99 μg m−3. During the cold fronts season, the greatest average concentration of p-xylene (0.98 μg m−3) was found in San Bernabe, while Santa Catarina reported the highest average for toluene at 1.55 μg m−3. A health risk assessment indicated that cancer risk coefficients exceeded the reference values set by the EPA. These findings suggest that the presence of the alkyl derivatives of benzene (benzene, toluene, ethylbenzene, and p-xylene) in the studied region poses a potential health issue and highlights the need for enhanced control measures regarding their sources.